Mineralisation controls in the Ultramafic Sequence and T Zone of the Waterberg Project, north of the Hout River Shear Zone, Bushveld Complex, South Africa - Mkhabela, Sehlabane Aleck (My University, 2021)
The Waterberg Project area is separated from the Northern Limb by the Hout River Shear Zone (HRSZ). Unlike the Northern Limb which unconformably overlies the Transvaal Supergroup and Archaean rocks of the Kaapvaal Craton, the Waterberg Project, located to the north of the HRSZ rests unconformably on granite-gneiss of the Southern Marginal Zone of the Limpopo Belt. The 1 100 m - 1 200 m thick magmatic succession strikes SW–NE and dips at 34–38° towards the NW. The 2.06 Ga succession is composed of basal Marginal pyroxenite sills, the Ultramafic Sequence (UmS), the Troctolite–Gabbronorite-Anorthosite sequence (TGA) and the Upper Zone (UZ). The entire succession is covered by thick 2.05 Ga – 1.95 Ga Waterberg Group sediments of the Setlaole (lower) and Makgabeng (upper) formations. Deposition of these sediments took place after an intense total erosion of the roof rocks and partial erosion of the Bushveld succession. The sedimentary succession was later succeeded by intrusions of 1.1 Ga dolerite sills linked to the Umkondo Igneous Province. Platinum-group element (PGE)-Au-Cu and Ni sulphide mineralisation within the succession is confined to both the lower Ultramafic Sequence (the F zone) and the upper portion of the TGA (the T Zone). This mineralisation is intimately associated with conspicuous blebby and disseminated sulphides, which are predominantly chalcopyrite, pentlandite and pyrrhotite with traces of bornite in places. Within the UmS, the mineralised interval varies from 3 m to 100 m in thickness; with grade occurring in both the lower feldspathic pyroxenite (FP) and the upper feldspathic harzburgite (FH). Based on the grade-thickness attributes, the UmS (F Zone) has been subdivided into five highly mineralised zones/districts. The thinnest and less mineralised F - South, the thickest and well mineralised F - Central, F - Boundary South, F - Boundary North and F - North. In both the F- Central and F – Boundary South, well defined floor embayments seem to have played a crucial role in shaping and defining the thicker mineralisation. The mineralisation in both the F - Boundary North and the F - North seems to have not been controlled by such embayments. Unlike all the four F Zone districts, mineralisation within the F - North is better defined and developed in the FP rather than the FH. The prevalence of FP xenoliths within the FH of the F - Central suggests intense thermo mechanical erosion, entrainment and resorption during multiple FH magma influxes. These xenoliths are less common within the F - North where the FP is well preserved. As for the T Zone, the highest grade mineralisation is within the lower subzone (T2) gabbronorite, transgressing up-dip from west to east and along strike from SW to NE into the Lower Pegmatoidal Anorthosite (LPA). Both the T2 and the LPA are well endowed with mineralisation while the upper subzone (T1) and Upper Pegmatoidal Anorthosite (UPA) mineralisation is inconsistent and spatially sporadic. A well mineralised T0 subzone (sensu amplo) has been locally identified in the UZ. This mineralisation transgresses up-dip from west to east and along strike from SW to NE into the upper portion of the UPA converging along strike and up-dip with the T2/LPA mineralisation. Overall, there is a lack of an upward decrease in tenor (that is PGE content in 100% sulphide) within the UmS. Instead, tenors are lower at the base of the UmS (FP), increasing upwards to higher levels towards the top of the FH. Since the sulphide content is higher than can be dissolved by intercumulus liquid, this implies that multiple UmS magma influxes gained their tenors elsewhere and were already rich in PGE sulphides when entering the resident magma chamber. Unlike in-situ segregation of sulphides observed in the Western Bushveld and T1 of Turfspruit, the sulphides within the UmS were probably transported and deposited as chonolithic crystal mush without undergoing segregation. Both lateral tenor variations and Cu/Pd variations seem to favour a westerly/SW feeder zone for the UmS magma influxes. There is some degree of variability in both tenors and Cu/Pd trends within the T Zone. However, the trends seem to favour a westerly/SW feeder zone with higher tenors in both T2 and the LPA. Unlike the UmS, there seems to be higher levels of lateral anti-correlations between PGEs and Au tenors; implying that the higher Au content observed within the T Zone were obtained from a different source. There is some lithostratigraphic and geochemical correlatability between mineralisation of the Waterberg Project and that of the distal Harriet’s Wish and far distal Aurora Projects. However, the Waterberg mineralisation is comparable to the Platreef of both Mogalakwena and Turfspruit. In contrast to the western-eastern Bushveld, which is Pt dominant with high rhodium credit, the Waterberg Project is Pd dominant with high gold credit
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for Master of Science degree in Economic Geology